Improvement of lupus-associated fatigue with modafinil: Report of two cases. (May 2021) - Korsten, Peter; Piantoni, Silvia
Fatigue is a frequently reported and disabling symptom in patients with systemic lupus erythematosus (SLE). The management of Lupus-associated fatigue (LAF) is complex and requires the exclusion of disease activity and comorbidities as potentially treatable causes. Standard of care recommendations includes psychological counselling and regular physical activity. However, many SLE patients still report the persistence of LAF despite these measures. Therefore, pharmacological management may be required, which has been insufficiently investigated in clinical trials. Here, we report two patients who improved with pharmacological treatment with modafinil (MODA), a central nervous system stimulant. Both patients had an overall low disease activity (SLEDAI-2K score of 0). Their FACIT fatigue scores were 15 and 20, respectively (with a maximum score of 52, where 52 indicates the best quality of life). With MODA treatment, the first patient's FACIT fatigue score improved from 15 to 42, the second patient's score from 20 to 37. In the latter patient, it returned to 21 after stopping the drug and increased back again to 37 after re-treatment. In conclusion, our report demonstrates, for the first time, that MODA treatment is a potential pharmacological treatment option in selected patients with LAF. Clinical trials in SLE are required to confirm our observations.